Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Which of these points lies on the line described by the equation below?

[tex]\( y - 5 = 6(x - 7) \)[/tex]

A. [tex]\((-7, -5)\)[/tex]

B. [tex]\((5, 7)\)[/tex]

C. [tex]\((-5, -7)\)[/tex]

D. [tex]\((7, 5)\)[/tex]


Sagot :

To determine which of the points lies on the line described by the equation [tex]\(y - 5 = 6(x - 7)\)[/tex], we need to check each point by substituting the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] coordinates into the equation and seeing if it holds true.

Point A: [tex]\((-7, -5)\)[/tex]

Substitute [tex]\(x = -7\)[/tex] and [tex]\(y = -5\)[/tex] into the equation:
[tex]\[ -5 - 5 = 6(-7 - 7) \][/tex]

Simplify both sides:
[tex]\[ -10 = 6(-14) \][/tex]
[tex]\[ -10 = -84 \quad \text{(This is false)} \][/tex]

So, point A does not lie on the line.

Point B: [tex]\((5, 7)\)[/tex]

Substitute [tex]\(x = 5\)[/tex] and [tex]\(y = 7\)[/tex] into the equation:
[tex]\[ 7 - 5 = 6(5 - 7) \][/tex]

Simplify both sides:
[tex]\[ 2 = 6(-2) \][/tex]
[tex]\[ 2 = -12 \quad \text{(This is false)} \][/tex]

So, point B does not lie on the line.

Point C: [tex]\((-5, -7)\)[/tex]

Substitute [tex]\(x = -5\)[/tex] and [tex]\(y = -7\)[/tex] into the equation:
[tex]\[ -7 - 5 = 6(-5 - 7) \][/tex]

Simplify both sides:
[tex]\[ -12 = 6(-12) \][/tex]
[tex]\[ -12 = -72 \quad \text{(This is false)} \][/tex]

So, point C does not lie on the line.

Point D: [tex]\((7, 5)\)[/tex]

Substitute [tex]\(x = 7\)[/tex] and [tex]\(y = 5\)[/tex] into the equation:
[tex]\[ 5 - 5 = 6(7 - 7) \][/tex]

Simplify both sides:
[tex]\[ 0 = 6(0) \][/tex]
[tex]\[ 0 = 0 \quad \text{(This is true)} \][/tex]

So, point D lies on the line.

In conclusion, the point that lies on the line described by the equation [tex]\(y - 5 = 6(x - 7)\)[/tex] is:

D. [tex]\((7, 5)\)[/tex]